Effectiveness Of Prenatal Yoga And Bl23 Acupressure On Back Pain In Third-Trimester Pregnancy - Sumarni Sumarni; Siti Mutoharoh; Juni Sofiana; Dinar Binugraheni Lestari (Jurnal Bina Cipta Husada, 2026)
Back pain is one of the most common complaints experienced by pregnant women during the third trimester due to physiological and biomechanical changes throughout pregnancy. This condition may reduce maternal quality of life, interfere with daily activities and sleep quality, and affect psychological well-being. Non-pharmacological management is considered the primary approach to reducing back pain during pregnancy, including prenatal yoga and BL23 point acupressure. This study aimed to analyze the effectiveness of a combination of prenatal yoga and BL23 acupressure in reducing back pain among third-trimester pregnant women. This study employed a case study design with a descriptive analytical approach. The research was conducted in Tegalrejo Village, Poncowarno District, in February 2026. The sample consisted of 9 third-trimester pregnant women experiencing back pain, selected using purposive sampling techniques. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. The intervention included prenatal yoga sessions for approximately 30 minutes followed by BL23 point acupressure for 3–5 minutes on each point, administered twice a week for two weeks. Data were analyzed descriptively by comparing pain intensity before and after the intervention. The results showed that before the intervention, 55.6% of respondents experienced moderate pain and 44.4% experienced mild pain. After the intervention, the proportion of respondents experiencing mild pain increased to 66.7%, while moderate pain decreased to 33.3%. These findings indicate that the combination of prenatal yoga and BL23 acupressure effectively reduced back pain intensity among third-trimester pregnant women. In conclusion, the combination of prenatal yoga and BL23 acupressure is effective as a non-pharmacological complementary therapy for reducing back pain in third-trimester pregnant women. This intervention is safe, easy to implement, and may improve maternal comfort and quality of life during pregnancy.